Bellevue : a novel - Cook, Robin, 1940- (G. P. Putnam's Sons, 2024)
"Twenty-three-year-old Michael 'Mitt' Fuller starts his surgical residency with great anticipation at the nearly three-hundred-year-old, iconic Bellevue Hospital, following in the footsteps of four previous, celebrated Fuller generations. The pressure is on for this newly minted doctor, and to his advantage he's always had a secret sixth sense, a sensitivity to the nonphysical. But quickly one patient after another assigned to his care begin to die from mysterious causes. As he tries to juggle these inexplicable deaths with the demands of being a first-year resident, things rapidly spiral out of control. Visions begin to plague Mitt--visions of a little girl in a bloodstained dress, bloodcurdling screams in the distance, and worse. As bodies mount and Mitt's stress level rises, he finds himself drawn to the monumental, abandoned Bellevue Psychopathic Hospital building, which to his astonishment has somehow defied the wrecking-ball and still stands a few doors north of the modern Bellevue Hospital high-rise. Forcing an unauthorized entry into this storied but foreboding structure, Mitt discovers he's more closely tied to the sins of the past than he ever thought possible"--